(untitled) (Journal of Hama University, 2022)
The experiment was carried out using two types of irrigation water: the water of the Euphrates River, which had an electrical conductivity of (ECf = 1.03 ds/m) and the water of the kidney well, which had an electrical conductivity of (ECw = 6.90 ds/m), and four levels of nitrogenous and organic fertilization (sheep waste). : (witness, nitrogen fertilizer (150 kg urea / h), fermented sheep waste at a rate of (10.165 tons / h), half the amount of nitrogen fertilizer 75 kg + half of the fermented sheep waste 5.083 tons / h), and the results of the statistical analysis showed that the treatment of the mutual effect of irrigation With the water of the Euphrates River and the addition of nitrogen fertilizer to the millet plant, the highest significant difference was recorded for the values ​​of productivity indicators (number of grains/plant - weight of (1000) grains - grain yield - protein/grain ratio - protein yield/grain), while the average was the lowest for the same indicators. In the treatment of overlapping irrigation with the water of the kidney well with the control treatment without fertilization.